Ethan Allen style create the look you love - Samon, Katherine Ann (Ethan Allen Marketing Corporation, 2002)
Create the look you love! How do you create rooms you'll love living in every day? Just look inside, Ethan Allen's design team has compiled more than twenty beautiful and distinct styles, each with pages of richly detailed photographs, filled with inspiration and information on design and history to help you-step by step-realize the looks you've dreamed of.